Influência da oxigenação e adição de fonte externa de carbono na remoção de nutrientes e contaminantes emergentes em sistema biológico AOA - Franzoni, Ruana Mendonça (2021)
The anaerobic-aerobic-anoxic (AOA) system has been studied by some authors who seek to improve the removal of recalcitrant nutrients and emerging contaminants for biological treatment. Positive results have already been found for the removal of nitrogen and phosphorus in some types of treatment, however, the removal of these nutrients and emerging contaminants for biological treatment is still a challenge. The objective of this work was to evaluate an AOA system in the removal of nitrogen, phosphorus and the emerging contaminants 17α-ethinylestradiol (EE2) and triclosan (TCS) from synthetic influent. The system consisted of anaerobic-aerobic-anoxic reactors in series, with upward flow and continuous flow, rectangular base and useful volume of 19.8 L each. The support medium used to adhere the biomass were polyvinyl chloride (PVC) corrugated rings for the anaerobic and aerobic reactors, and red ceramic residues in the anoxic reactor. The system was operated in two stages: with an 8-hour TDH and a flow rate of 2.40 L h-1 for the three reactors. In Step 1, with air flow in the aerobic reactor of 5 L min-1 and with intermittent aeration, of 3 hours on and 1 hour off. In Step 2, the system was operated with an air flow in the aerobic reactor of 10 L min-1 and with intermittency of aeration, of 1 hour and 30 minutes on and 30 minutes off, and addition of glucose in the anoxic reactor as an external source of carbon with a concentration of 190 mg L-1. In Step 1, the system achieved average removals of raw COD, TAN, TKN, TP, EE2 and TCS, of 97.07%, 13.37%, 49.43%, 12.24%, 48.45% and 87.10%, respectively. In step 2, the average removal efficiencies achieved were 95.62% for crude COD, 88.30% for TAN, 85.29% for TKN, 20.15% for TP, 81.68% for EE2 and 93.13% for TCS. It was possible to conclude that the change in the concentration of DO in the aerobic reactor, due to the change in the intermittency of the aeration, and the addition of glucose in the anoxic reactor, in Step 2, contributed to improve the performance of the system, increasing the removal efficiencies of both of the nutrients and emerging contaminants. It was also observed that the removal of EE2 is directly related to the nitrification and denitrification processes. In the analysis of the microbial community of the system, the phyla found in greater abundance were Proteobacteria, Firmicutes and Bacteroidetes. Furthermore, the main genera identified in the system were f_Veillonellaceae, Anaeromusa, Aeromonas, Azospira and Clostridium. Finally, it is concluded that the identified organisms, regarding phylum and genus in the microbial community of the AOA system, correspond with the recognized activities and with the removal performance achieved; and the main difference in the microbial community between the three reactors was through the oxygenation of each reactor.